Regional Economic Outlook, October 2015 : Western Hemisphere Department: Adjusting Under Pressure. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2015)
Economies in the Western Hemisphere are generally seeing a slowdown in growth. The U.S. economy regained momentum after a slow start at the beginning of the year, while in Latin America and the Caribbean economic activity continues to decelerate. Stronger U.S. growth should benefit countries in the region, especially those with tighter links through trade, remittances, and tourism (Mexico, Central America, and the Caribbean). Weaker commodity prices for the foreseeable future, however, will continue to hurt South America's net commodity exporters, lowering national incomes, reducing investment, and worsening fiscal balances. These developments could, in turn, impede progress made in recent years in poverty reduction. These developments could, in turn, impede progress made in recent years in poverty reduction. Key risks, including an abrupt tightening of U.S. interest rates or a further slowdown in China, may disproportionately affect Latin America. Chapters in this report examine monetary policy in Latin America, including the region's exposure to global financial shocks; the role of value chains and regional trade agreements in fostering trade integration; and financial market development in the region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet